Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional, Komisaris Independen, dan Leverage terhadap Integritas Laporan Keuangan - Lia Azzah (Universitas Negeri Surabaya, 2021)
This study aims to examine the effect of managerial ownership, institutional ownership, independence commissioner, and leverage on the integrity of financial statements. The population of this research is the mining sector companies and consumer goods industry companies listed on the Indonesia Stock Exchange (IDX) in 2015 2018. The sampling method is pusposive sampling. There are 97 mining and consumer goods industry companies used as samples. The data analysis used multiple linear regressions. The result shows that managerial ownership, institutional ownership, and independence commissioner has positive significant influence on integrity of financial statements. Leverage has no influence on integrity of financial statements.